Sources and Effects of Fluids in Continental Retrograde Shear Zones: Insights from the Kuckaus Mylonite Zone, Namibia. (1st August 2020) - Stenvall, C. A.; Fagereng, A.; Diener, J. F. A.; Harris, C.; Janney, P. E.
Abstract : Midcrustal rocks in retrograde metamorphic settings are typically H2 O-undersaturated and fluid-absent and have low permeability. Exhumed continental retrograde faults, nonetheless, show evidence for the operation of fluid-mediated weakening mechanisms during deformation at midcrustal conditions. To explore the origin and effects of fluids in retrograde faults, we study the Kuckaus Mylonite Zone (KMZ), an exhumed crustal-scale, strike-slip shear zone in the southern Namibian Namaqua Metamorphic Complex. The KMZ deformed quartzofeldspathic migmatised gneisses at midcrustal retrograde conditions (450-480°C, 270-420 MPa) in the Mesoproterozoic, 40 Ma after granulite facies peak metamorphism at 825°C and 550 MPa. The mylonites contain fully hydrated retrograde mineral assemblages, predominantly adjacent to anastomosing high-strain zones, providing evidence of local H2 O saturation and fluid presence during deformation. Whole rock and quartz vein δ 18 O values suggest that at least some of the fluids were meteoric in origin. The rocks across the shear zone retain the effect of different protoliths, implying little effect of fluid-rock interaction on whole rock major element chemistry. Together with a general scarcity of quartz veins, this suggests that fluid/rock ratios remained low in the KMZ. However, even small amounts of H2 O allowed reaction weakening and diffusion-precipitation, followed by growth and alignment of phyllosilicates. In the ultramylonites, a fine grain size in the presence of fluids allowed for grain size sensitive creep. We conclude that the influx of even small volumes of fluids into retrograde shear zones can induce drastic weakening by facilitating grain size sensitive creep and retrograde reactions. In retrograde settings, these reactions consume fluids, and therefore elevated fluid pressures will only be possible after considerable weakening has already occurred. Our findings imply that the range of seismic styles recently documented at active retrograde transform faults may not require high fluid pressures but could also arise from other local weakening mechanisms.